An applicable approach for performance auditing in ERP - Wan Jian Guo; Li Ting Liao (MATEC Web of Conferences, 2016)
This paper aims at the realistic problem of performance auditing in ERP environment. Traditional performance auditing methods and existing approaches for performance evaluation of ERP implementation could not work well, because they are either difficult to work or contains certain subjective elements. This paper proposed an applicable performance auditing approach for SAP ERP based on quantitative analysis. This approach consists of 3 parts which are system utilization, data quality and the effectiveness of system control. In each part, we provide the main process to conduct the operation, especially how to calculate the online settlement rate of SAP system. This approach has played an important role in the practical auditing work. A practical case is provided at the end of this paper to describe the effectiveness of this approach. Implementation of this approach also has some significance to the performance auditing of other ERP products.